When spider and snake get along: Fusion of a snake disintegrin with a spider phospholipase D to explore their synergistic effects on a tumor cell. (October 2019) - Siqueira, Raquel A.G.B.; Calabria, Paula A.L.; Caporrino, Maria C.; Tavora, Bianca C.L.F.; Barbaro, Katia C.; Faquim-Mauro, Eliana L.; Della-Casa, Maisa S.; Magalhães, Geraldo S.
Abstract: Venoms of spiders and snakes contain toxins extremely active and, thus, provide a natural source for the development of new biotechnological tools. Among the diversity of toxins present in the venom of spiders from genus Loxosceles, the phospholipases D (PLDs) show high hydrolytic activity upon lysophosphatidylcholine (LPC) and sphingomyelin (SM), generating bioactive phospholipids such as cyclic phosphatidic acid (cPA). Since this mediator has been shown to play a major role in complex signaling pathways, including inhibition of tumor cells, the PLDs may hold the key to learn how toxins could be used for therapeutic purposes. However, the strong platelet aggregation of PLDs and their lack of selectivity impose a major limitation. On the other hand, disintegrins present in the venoms of Viperidae snakes are a potent inhibitor of platelet aggregation and possess high affinity and specificity to molecules called integrins that are highly expressed in some tumor cells, such as murine melanoma B16F10. Therefore, disintegrins might be suitable molecules to carry the PLDs to the malignant cells, so both toxins may work synergistically to eliminate these cells. Thus, in this work, a recombinant PLD from Loxosceles gaucho spider was recombinantly fused to a disintegrin from Echis carinatus snake to form a hybrid toxin called Rechistatin. This recombinant toxin was successfully expressed in bacteria, showed binding activity in B16F10 murine melanoma cells and exerted a synergistic cytotoxicity effect on these cells. Therefore, the approach presented in this work may represent a new strategy to explore new potential applications for spider PLDs. Highlights: Hybrid toxin Rechistatin suppressed platelet aggregation at higher doses. Rechistatin was able to bind to murine B16F10 melanoma cells. Rechistatin showed cytotoxicity on B16F10 melanoma cells.